Mental Health in Prisons Critical Perspectives on Treatment and Confinement (Palgrave Studies in Prisons and Penology, 2018)
This book examines how the prison environment, architecture and culture can affect mental health as well as determine both the type and delivery of mental health services. It also discusses how non-medical practices, such as peer support and prison education programs, offer the possibility of transformative practice and support. By drawing on international contributions, it furthermore demonstrates how mental health in prisons is affected by wider socio-economic and cultural factors, and how in recent years neo-liberalism has abandoned, criminalised and contained large numbers of the world's most marginalised and vulnerable populations. Overall, this collection challenges the dominant narrative of individualism by focusing instead on the relationship between structural inequalities, suffering, survival and punishment. Chapter 2 is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.